The multifaceted regulatory roles of Nudix hydrolases in cancer and their therapeutic potential - Pan, Jianguo; Yang, Jiaxi; Wang, Kewei (Frontiers in Oncology, 2026)
The NUDT family comprises evolutionarily conserved enzymes that hydrolyze diverse substrates, including nucleoside phosphates, inositol polyphosphates, and RNA caps. Contrary to earlier perspectives focusing primarily on genome protection, compelling evidence now indicates that the majority of NUDT function as pro-tumorigenic factors. Cancer’s complex landscape, characterized by uncontrolled proliferation, evasion of apoptosis, metabolic reprogramming (like the Warburg effect), and genomic instability, creates an environment where NUDT exert significant influence. Key NUDT members, such as MTH1 (NUDT1), NUDT5, NUDT15, and NUDT22, are frequently overexpressed in cancers and actively promote tumor survival and progression. They achieve this not only by “sanitizing” the nucleotide pool to maintain genomic stability in cancer cells (hydrolyzing damaged nucleotides/caps), but also by dysregulating critical signaling pathways. The relationship between NUDT and cancer is multifaceted, involving intricate roles in nucleotide metabolism, redox homeostasis, and DNA repair. This functional diversity underscores their potential as therapeutic targets. Pharmacological inhibition of specific NUDT, particularly MTH1 and NUDT5, is an active area of research. Such inhibition aims to exploit cancer cell vulnerabilities by increasing the accumulation of damaged nucleotides and enhancing susceptibility to DNA-damaging agents (e.g., chemotherapy, radiotherapy) or PARP inhibitors, offering promising avenues for novel combination therapies. This review comprehensively overviews the mechanisms, diverse functions, and pathophysiological roles of NUDT in cancer biology, critically evaluating their therapeutic potential and the challenges in targeting them.